UNDERSTANDING LOW ACHIEVER STUDENTS’ LINGUISTIC AND COGNITIVE PROBLEMS IN WRITING ENGLISH DESCRIPTIVE TEXT - Euis Rina Mulyani; Mu'man Mu'man (PROJECT (Professional Journal of English Education), 2024)
Students’ competence in writing skills plays a significant role in leading them to success in learning English. However, in reality, many Indonesian students experience problems in creating quality texts, in particular descriptive ones. This study aims to examine low-achiever students' problems in writing descriptive text. The study was conducted in a private Senior High School in Bandung. The data was gained from eight students' works on descriptive text. They were obtained from their English teacher. The data was analyzed qualitatively using Miles & Huberman’ (1991) framework of qualitative data analysis, Jacobs et al’s (1981) components of writing, and Byrne’s (1998) types of writing difficulty. The finding shows that the students experienced serious linguistic and cognitive problems in writing the text, in particular in the areas of content, language use, organization, vocabulary, and mechanics.  Finally, this finding implies that (1) teaching writing should emphasize the process rather than the product, and (2) providing knowledge of autonomous learning to students is essential so that students can learn and practice writing independently outside the classroom.